5x-(-2)=12

Simple and best practice solution for 5x-(-2)=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-(-2)=12 equation:


Simplifying
5x + -1(-2) = 12

Multiply -1 * -2
5x + 2 = 12

Reorder the terms:
2 + 5x = 12

Solving
2 + 5x = 12

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + 5x = 12 + -2

Combine like terms: 2 + -2 = 0
0 + 5x = 12 + -2
5x = 12 + -2

Combine like terms: 12 + -2 = 10
5x = 10

Divide each side by '5'.
x = 2

Simplifying
x = 2

See similar equations:

| h=-16t^2-13t+200 | | -9y+3+2x-9y-8= | | 4134.4=646n | | 4s=1s+13 | | n/10=15 | | -20=9x | | (3x-3)(x+7)= | | x+(x-11)=73 | | 7w+6w=25 | | 3(6n-1)=123 | | -5+25-r=25 | | m/10=19 | | -21=c/3 | | -3-6x=-51 | | 6a+7b=69 | | 42/0.4 | | -10=5/6n-7-1/3n | | l+3+4xw= | | 2(p+13)+7=8(5-p)-3(-7-3p)+4 | | n/19=16 | | 1.6x-1.3x-1=8 | | X-30=125 | | (-4x+11)= | | 3(2a+b-3c)= | | (x+4)+(3x-7)= | | k/2=-20 | | (2x+10)2=(3x-55)2 | | -1+3.3h=-16 | | (8x)0(8x)= | | 50+6m= | | 9+x=-8x-18 | | X=50-46 |

Equations solver categories